The cortisol awakening response and major depression: examining the evidence - Dedovic K (Dove Medical Press, 2015)
Katarina Dedovic,1,2 Janice Ngiam3 1Department of Psychiatry, Douglas Hospital Research Centre, Montreal, QC, Canada; 2Social and Affective Neuroscience Laboratory, University of California, Los Angeles, CA, USA; 3Department of Psychology, McGill University, Montreal, QC, Canada Abstract: A vast body of literature has revealed that dysregulation of the hypothalamic–pituitary–adrenal (HPA) stress axis is associated with etiology of major depressive disorder (MDD). There are many ways that the dysregulation of the HPA axis can be assessed: by sampling diurnal basal secretion and/or in response to a stress task, pharmacological challenge, and awakening. Here, we focus on the association between cortisol awakening response (CAR), as one index of HPA axis function, and MDD, given that the nature of this association is particularly unclear. Indeed, in the following selective review, we attempt to reconcile sometimes-divergent evidence of the role of CAR in the pathway to depression. We first examine association of CAR with psychological factors that have been linked with increased vulnerability to develop depression. Then, we summarize the findings regarding the CAR profile in those with current depression, and evaluate evidence for the role of CAR following depression resolution and continued vulnerability. Finally, we showcase longitudinal studies showing the role of CAR in predicting depression onset and recurrence. Overall, the studies reveal an important, but complex, association between CAR and vulnerability to depression. Keywords: HPA axis, MDD, SCN, daily hassles, genetic influence, environmental factors